Analysis of the Doxorubicin and Doxorubicinol in the Plasma of Breast Cancer Patients for Monitoring the Toxicity of Doxorubicin - Harahap Y; Ardiningsih P; Corintias Winarti A; Purwanto DJ (Dove Medical Press, 2020)
Yahdiana Harahap,1 Puspitasari Ardiningsih,1 Agatha Corintias Winarti,1 Denni Joko Purwanto2 1Faculty of Pharmacy, Universitas Indonesia, Depok, Indonesia; 2Functional Medical Staff of Surgical Oncology, “Dharmais” Cancer Hospital, Jakarta, IndonesiaCorrespondence: Yahdiana Harahap Email yahdiana03@yahoo.comIntroduction: Doxorubicin is an anthracycline antibiotic used as an anticancer agent. Long-term use of this anticancer agent could accumulate its metabolite, doxorubicinol, and cause cardiomyopathy, due to its cardiotoxicity. This cardiotoxic effect depends on the amount of doxorubicin and doxorubicinol accumulated in the body. This study aimed to analyze doxorubicin and doxorubicinol levels in the blood plasma of breast cancer patients.Methods: Participants of this study were 30 breast cancer patients who had received doxorubicin in their therapy regimen. The samples were analyzed using ultra-high performance liquid chromatography-tandem mass spectrometry (LC-MS/MS), with the Acquity UPLC BEH C18 Waters chromatography column (2.1 x 100 mm : 1.7 μm). Plasma (250 μL) samples were prepared by protein precipitation, using methanol. The mobile phase consisted of 0.1% acetic acid (eluent A) and acetonitrile (eluent B), with gradient elution; the flow rate was 0.15 mL/min and runtime, 7 min.Results and Discussion: This method was linear in the range of 1– 1000 ng/mL for doxorubicin and 0.5– 500 ng/mL for doxorubicinol. This method was successfully used to analyze doxorubicin and doxorubicinol, simultaneously, using hexamethylphosphoramide as the internal standard, in the plasma of breast cancer patients. Results showed that the measured concentrations of doxorubicin and doxorubicinol ranged between 12.54– 620.01 ng/mL and 1.10– 27.00 ng/mL, respectively. The measured cumulative doses of doxorubicin ranged between 48.76 and 319.01 mg/m2; thus, the risk of cardiomyopathy in the surveyed patients was under 4%, according to literature.Keywords: analysis, breast cancer, cardiotoxic, doxorubicin, doxorubicinol, partial validation, plasma, LC-MS/MS